2019
DOI: 10.1155/2019/8203832
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Screening and Toxicological Study of Aristolochia baetica Linn Roots: Histopathological and Biochemical Evidence

Abstract: Aristolochia baetica (A. baetica) is a wild species of Aristolochiaceae family; its roots are used by Moroccan people against cancer for many years ago. The objective of the study was to investigate the phytochemical screening, acute and subacute toxicity of A. baetica roots growing in the north of Morocco. Qualitative and quantitative analyses of A. baetica roots were performed using standard methods; the acute toxicity of the root extract of the studied plant was assessed in mice by gavage of single doses of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 24 publications
3
12
0
Order By: Relevance
“…As reported in the literature, there are very little reported cases of acute human or animal poisoning by Aristolochia species [21]; however, plants of Aristolochiaceae family are considered as most dangerous herbs when consumed for a long period due to their content of aristolochic acids (AAs). The distribution of these compounds appears to be homogenous within the genus and could here account for the strongly positive reaction observed for alkaloids with Dragendorff's reagent during our phytochemical screening [22, 23]. The findings of acute toxicity revealed that the mortality was remarked in treated animals with the great dose only (4g/kg) responsible for 50% of animals mortality.…”
Section: Discussionmentioning
confidence: 77%
“…As reported in the literature, there are very little reported cases of acute human or animal poisoning by Aristolochia species [21]; however, plants of Aristolochiaceae family are considered as most dangerous herbs when consumed for a long period due to their content of aristolochic acids (AAs). The distribution of these compounds appears to be homogenous within the genus and could here account for the strongly positive reaction observed for alkaloids with Dragendorff's reagent during our phytochemical screening [22, 23]. The findings of acute toxicity revealed that the mortality was remarked in treated animals with the great dose only (4g/kg) responsible for 50% of animals mortality.…”
Section: Discussionmentioning
confidence: 77%
“…Aristolochia baetica (Figure 7) and Aristolochia paucinervis ( Figure 8), used for cancer treatment in the region of Greater Casablanca, were the most toxic plants [22, 37]. The toxic effects of these medicinal plants or their derivatives like aristolochic acids were largely investigated in several literatures [38].…”
Section: Resultsmentioning
confidence: 99%
“…On day 28, the animals were sacrificed after anesthesia for blood and organ collection. Organ weights were estimated to calculate the relative weight of organs [ 22 ].…”
Section: Methodsmentioning
confidence: 99%